Effect of CO2 on the catalytic performance of Zn/ZSM-5 towards the conversion of methanol to aromatics. (15th January 2023) - Jin, Runze; Ma, Ke; Chen, Zhongshun; Tang, Zhongqiang; Hu, Haobin; Wang, Jiaofei; Zhang, Zhuangzhuang; Dai, Chengyi; Ma, Xiaoxun
Graphical abstract: Highlights: CO2 is used as hydrogen atom acceptor to consume the surplus hydrogen in the process of methanol to aromatics. It is proved that ZnO is the active site for CO2 conversion and ZnOH + is the central site for methanol aromatization. The performance of methanol aromatization in CO2 atmosphere is affected by CO2  + H2 ability and methanol aromatization ability. Abstract: The selectivity of methanol conversion to aromatics on Zn/ZSM-5 is often limited, mainly because the hydrogen removed during the process combines with low-carbon olefin intermediates to regenerate alkanes and reduce the effective utilization of carbon atoms. Herein, CO2 is added to the methanol aromatization reaction as a receptor that consumes hydrogen in situ, which reduces the hydrogen transfer reaction and improves the selectivity of aromatics. It is proposed that aromatic selectivity under CO2 atmosphere is determined by the chemical state of Zn species. Specifically, ZnO converts CO2 and consumes hydrogen, and ZnOH + promotes methanol aromatization. Under the same conditions, aromatic selectivity of 3ZnZ18-IM under CO2 atmosphere can reach 85.2 %, which is much higher than that of 71.4 % under N2 atmosphere. This study provides a new strategy for methanol to aromatics (MTA) reaction, which has a positive impact on solving the energy and environmental problems in the production of aromatics.